2019
DOI: 10.1016/j.bbr.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Subtle behavioral changes and increased prefrontal-hippocampal network synchronicity in APPNL−G−F mice before prominent plaque deposition

Abstract: Amyloid-β (Aβ) peptides occur in the brains of patients with Alzheimer's disease (AD), but their role in functional impairment is still debated. High levels of APP and APP fragments in mice that overexpress APP might confound their use in preclinical research. We examined the occurrence of behavioral, cognitive and neuroimaging changes in APP knock-in mice that display Aβ42 amyloidosis in the absence of APP overexpression. Female APP mice (carrying Swedish, Iberian and Arctic APP mutations) were compared to AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 49 publications
8
83
2
1
Order By: Relevance
“…However, unlike us, they compared App NL-G-F KI mice behaviour to that of App NL KI mice only, and not to control WT mice. They found App NL-G-F KI mice spent more time in the open arms at 6 months of age (Latif-Hernandez et al, 2017), which we replicated at 8 months of age. A very recent study has also found that 6-9 month old App NL-G-F KI mice spent more time in the elevated plus maze open arms (Sakakibara et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…However, unlike us, they compared App NL-G-F KI mice behaviour to that of App NL KI mice only, and not to control WT mice. They found App NL-G-F KI mice spent more time in the open arms at 6 months of age (Latif-Hernandez et al, 2017), which we replicated at 8 months of age. A very recent study has also found that 6-9 month old App NL-G-F KI mice spent more time in the elevated plus maze open arms (Sakakibara et al, 2018).…”
Section: Discussionsupporting
confidence: 70%
“…Accordingly, any dysfunction found in App NL-F KI but not App NL-G-F KI mice of ~9 months age, as here, can reasonably be attributed as the sequelae of specifically insoluble Aβ 42 aggregation. We therefore argue that specifically insoluble Distance travelled in the open field is significantly greater in 6 month old App NL-G-F KI mice, whilst at 8 months (the current study) and 10 months of age, there were no significant differences (Latif-Hernandez et al, 2017;Whyte et al, 2018), suggesting hyperactivity is only detectable in younger mice.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations